2019
DOI: 10.1038/s41398-019-0510-x
|View full text |Cite
|
Sign up to set email alerts
|

The onset of sleep disturbances and their associations with anxiety after acute high-altitude exposure at 3700 m

Abstract: Sleep disturbances and psychiatric repercussions pose great challenges at high altitude; however, few studies have investigated sleep disturbance and anxiety profiles and their associations after acute exposure in consecutive patients. Thus, we aimed to study the profiles of sleep disturbances in consecutive patients after high-altitude exposure and the association of such disturbances with anxiety. A total of 668 participants were recruited at sea level and 3700 m. The trials were performed at sea level (1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…A negative correlation between the efficiency of sleep and depression was also observed. Bian et al ( 43 ) showed that SDB developed at HA was positively correlated with anxiety, and the synthesis of amines, substance P, catecholamines, and nitric oxide was affected due to breathing disruption during sleep, which is related to mood disturbances, anxiety, and stress. Reviewing previous literature, reactions, attention, and mood are significantly impaired during the first 1 to 2 weeks after an individual ascends to a high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation between the efficiency of sleep and depression was also observed. Bian et al ( 43 ) showed that SDB developed at HA was positively correlated with anxiety, and the synthesis of amines, substance P, catecholamines, and nitric oxide was affected due to breathing disruption during sleep, which is related to mood disturbances, anxiety, and stress. Reviewing previous literature, reactions, attention, and mood are significantly impaired during the first 1 to 2 weeks after an individual ascends to a high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…With very few exceptions ( Szymczak et al, 2009 ; Johnson et al, 2010 ; Frost et al, 2021 ), sleep studies conducted at altitude have included primarily men ( Pattyn et al, 1985 ; Bolmont et al, 2000 ; Stadelmann et al, 2013 ; Fernandez Tellez et al, 2014 ; Rojc et al, 2014 ; Morrison et al, 2017 ; Bian et al, 2019 ; Mairesse et al, 2019 ). This is remarkable, as it is clear that sex does lead to significant differences in the outcomes of psychophysiological research ( Mark et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many normobaric hypoxic ( Rojc et al, 2014 ; Morrison et al, 2017 ) and hypobaric hypoxic field ( Reite et al, 1975 ; Bloch et al, 1985 ; Pattyn et al, 1985 ; Szymczak et al, 2009 ; Johnson et al, 2010 ; Stadelmann et al, 2013 ; Fernandez Tellez et al, 2014 ; Bian et al, 2019 ; Mairesse et al, 2019 ) and laboratory ( Anholm et al, 1992 ; Houston, 1997 ; Richalet, 2010 ) studies have focused on the analysis of sleep at altitude, confirming that with increasing altitude there is also an increased level of sleep disturbance. Regarding the combination of hypoxia and bed rest (BR) far less research has been performed ( Rojc et al, 2014 ; Morrison et al, 2017 ; Gennser et al, 2018 ).…”
Section: Introductionmentioning
confidence: 94%
“…The English version of the scale was compiled by Zung in 1971 21 and localised by Chinese scholars in 1981, making it appropriate to use in the Chinese population; 22 it has since been widely used. [23][24][25] This scale contains a total of 20 items measured on a 4-point Likert scale, ranging from 1 (none or a little of the time) to 4 (good all of the time). The standard score for the scale was obtained by multiplying the original score of 20 items by 1.25.…”
Section: Self-rating Anxiety Scale (Sas)mentioning
confidence: 99%